A Note on Yahwistic Personal Names in the Murašû Texts - Stolper, Matthew W.
initial yhw-, Ia-a-ḫu-û-, Ia-a-ḫu-, Ia-ḫu-ú-, Ḫu-ú-, indicating (Ya)hū-; final -ia-a-ma, -ia-ma, -a-ma, -yh, indicating -yā or -yô or -yaw.